(untitled) (Research, Society and Development, 2021)
The present work aimed to review the potentialities of the use of Narrative Medicine (MN) as a concept to intensify and qualify the learning and clinical reasoning of medical students, in the context of the teaching-learning process. For this, a literature search was carried out with well-defined search criteria, in the SciELO and LILACS databases, using the descriptors: “Medicina Narrativa AND Educação Médica” and “Medicina Narrativa AND Humanização”. The analysis of seventeen articles revealed that narrative in medicine works as a guide capable of awakening and facilitating the interpretation of clinical cases in the context of a specific disease, based on content developed by the dialogical and hermeneutic dimension of clinical practice. It was identified that the art of selecting the most appropriate medical maxim for a particular clinical decision is acquired mainly through the accumulation of case experiences collected in the dialogues with patients. Furthermore, it is considered that each patient experiences the disease in a unique and contextual way, challenging the aspiring physician to experience this MN and to associate clinical learning and semiology reasoning in formulating hypotheses and appropriate treatments for their patients’ diseases. It is concluded that MN represents an important resource in the production of knowledge, whether from the perspective of teaching, research and care, allowing the humanistic training of physicians, in a construction of critical awareness about themselves, the profession and society, through dialogues about the existence of patients, social and complex aspects based on vulnerability and the process of illness and cure.